étude de l'élimination des fluorures des eaux par l'électrocoagulation - رابعة, كحيحة; أفراح, باوية; خضرة, بدرة (University of El-Oued, 2022)
"Abstract The effects of mineral salts on water quality, beneficial or harmful depending on their concentration. In many countries, there are areas where certain waters contain high levels of fluorides and have a negative impact on human health. In this work, the removal of fluorides from groundwater by electrocoagulation was studied. The effect of current density and stirring time on the treatment efficiency was examined. The results obtained showed that EC is capable of considerably reducing the level of fluoride in groundwater initially containing 3.1 mg/L of F - . The defluoridation of water increases slowly with reactor agitation time and with increasing current intensity. The maximum removal efficiency of F - reached 94.5% after two hours (for I = 40 mA). Therefore, EC can be considered as an alternative process to conventional techniques for the treatment of fluoride-laden water. ""الملخص تأثير الأملاح المعدنية على جودة المياه مفيد أو ضار حسب تركيزها. في العديد من البلدان ، توجد مناطق تحتوي فيها مياه معينة على مستويات عالية من الفلورايد ولها تأثير سلبي على صحة الإنسان. في هذا العمل ، تم التحقيق في إزالة الفلوريدات من المياه الجوفية عن طريق التخثير الكهربائي. تم فحص تأثير كثافة التيار وزمن التقليب على كفاءة المعالجة. أظهرت النتائج التي تم الحصول عليها أن المفوضية الأوروبية قادرة على تقليل مستوى الفلوريد بشكل كبير في المياه الجوفية التي تحتوي في البداية على 3.1 مجم / لتر من F-. يزداد نزع فلورة الماء ببطء مع وقت تحريض المفاعل ومع زيادة شدة التيار. أقصى كفاءة إزالة لـ F- وصلت إلى 94.54٪ بعد ساعتين (لـ I = 40 مللي أمبير). لذلك ، يمكن اعتبار EC كعملية بديلة للتقنيات التقليدية لمعالجة المياه المحملة بالفلوريد. "
مذكرات ماستر تخصص ري
Keywords: Key words: fluoride, electrocoagulation, groundwater, current, stirring time.; الكلمات المفتاحية: الفلورايد ، التخثير الكهربي ، المياه الجوفية ، التيار ، زمن التحريك.